Analysis of PT Pertamina's (Persero) Communication Strategy in Facing the Oplosan Issue Crisis - Rachel Zahra Safira; Sylvia A. Ronnfeld; Sophia Bernadette; Bertha Yunita Permatasari (International Journal Labs, 2026)
The fuel adulteration issue involving PT Pertamina (Persero) has become a significant crisis that threatens public trust and the company’s reputation as a strategic state-owned enterprise in Indonesia. Crisis management is not only related to resolving operational problems but also requires effective communication strategies to maintain organizational legitimacy. This study aims to analyze Pertamina’s communication strategy in addressing the fuel adulteration crisis through the perspective of Situational Crisis Communication Theory (SCCT). This research employed a qualitative descriptive approach with a case study design. Data were collected through semi-structured interviews with internal company representatives, consumers, and crisis communication experts, supported by documentation and media analysis. Data validity was ensured through source, method, and investigator triangulation, while thematic analysis was applied based on SCCT dimensions, including crisis identification, intensifying factors, and response strategies. The findings indicate that the crisis was categorized as a preventable crisis due to public perceptions regarding weaknesses in organizational supervision. Pertamina implemented a combination of diminish, rebuild, and reinforcing strategies by providing clarification, supporting legal investigations, improving two-way communication, and strengthening corporate reputation through educational communication. However, the effectiveness of these strategies was still influenced by response speed, message consistency, and transparency. This study concludes that crisis communication strategies in state-owned enterprises require a balanced approach between reputation protection and public accountability to restore stakeholder trust.